Facilitation of stereoscopic depth perception by a relative-size cue in ambiguous disparity stereograms. - Fineman, Mark B. (Journal of Experimental Psychology, 1971)
Proposed that the cue of relative size may facilitate depth perception in accordance with a crossed or uncrossed disparity in stereograms in which both tendencies are equally represented. A concurrent concept was that the latency associated with the perception of depth in random-dot stereograms may be due, in part, to a cue conflict between binocular disparity and relative size. 4 male and 2 female graduate students were given 8 presentations of 5 stereographic stimuli, in which disparity was ambiguous but relative size was systematically altered. Ss were tested for direction of depth preferences and response latency. Both the relative-size effects and an uncrossed disparity bias were evidenced in the data. The latter effect was attributed to binocular rivalry between dissimilar elements in the stereoscopic half-fields. It is concluded that depth cue relationships are more complex than had been suggested by simple dominance theories. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1971 American Psychological Association.
Keywords: Conflict (Psychology); Cues; Depth Perception; Female; Form Perception; Human; Male; Reaction Time; Size Perception; Vision; article; association; conflict; dept.psy; depth perception; female; human; male; pattern recognition; perception; reaction time; steroscopic depth perception facilitation, relative-size cue in ambiguous disparity stereograms; vision